Envisioning scenarios in designs for Networked Learning: Unfolding value tensions between technology and social learning - Jensen, Camilla Gyldendahl; Riise Clausen, Nicolaj; Dau, Susanne; Brogaard Bertel, Lykke; Ryberg, Thomas (Proceedings of the International Conference on Networked Learning, 2024)
This article presents an application of a design methodology to envision implicit value hierarchies in the design process of a digital learning platform meant to encompass learning processes and activities conducive to experiential collaborative learning (ECL). The authors argue that many technologies for the field of education fall short of their purposes and neglect intended underpinning pedagogy and didactics. Previous research efforts in networked learning have primarily focused on conceptual critiques of the implementation of EdTech and warned of technological euphoria undermining relevant caution. This means, that when a design team tries to conceptualize technological artefacts into a script the more ethical and value-oriented parts of the learning process tend to be ignored. While we agree with the conceptual critiques, our approach has instead been to engage with the design process and implement appropriate methodologies in an attempt to highlight implicit value hierarchies in the underlying learning theory. When using technologies in Networked learning we thus emphasize that both designers and stakeholders should engage in a systematic discussion and reflection of values and related judgements while constructing a value hierarchy. Through a Value-based design methodology based on semantic zooming we thus present 7 interconnected envisioning scenarios developed in the UnFoLD project to demonstrate how it is possible to operationalize values into detailed design briefs or technological scripts. This article will through presented experiences from a design process, show how the methodology of envisioning scenarios can be applied to mitigate the risks of implementation technology in a learning situation. We argue that an awareness and mapping of values as a part of the design process is essential and that an increased focus on the ethical and moral responsibilities of designers and involved researchers are important as technologies should not be seen as isolated, value-neutral, or uncomplicated translations of analogue teaching activities. The purpose of the article is to inspire other researchers and designers to implement value hierarchies, envisioning scenarios, or other similar methods to ensure that pedagogical and didactic priorities are not lost in accommodating marketability, practicalities, or technological constraints.